The Problems and Strategies of Life Insurance Marketing in China - Fangyan Feng (Law and Economy, 2022)
With the rapid development of economy and the continuous improvement of people’s material living standards, social production and life have entered the stage of prosperity. While focusing on improving the quality of life, people have also strengthened their awareness of hardship and crisis. Life insurance plays an increasingly important role in people’s lives in China. The marketing models and strategies of life insurance are constantly innovating and developing, which is both an opportunity and a challenge for China’s life insurance industry. With the continuous development of China’s insurance industry, insurance has been widely known to the public, and life insurance, as the most directly related product to people’s health, survival, and development, has gradually penetrated into people’s lives. However, in the life insurance marketing link, there are still some problems that customers are not completely satisfied with. Therefore, it should find out the corresponding solutions and improvement strategies through the existing problems of life insurance marketing in China, so as to promote the development of the life insurance industry and the entire insurance industry. In the thesis, the author firstly introduced the connotation and current situation of life insurance and its marketing in China, then the author analyzed the characteristics of life insurance marketing and the existing problems of its marketing in China. At last, the author proposed the improvement methods of life insurance marketing from four aspects.